2019
DOI: 10.1088/1475-7516/2019/12/037
|View full text |Cite
|
Sign up to set email alerts
|

Towards a viable effective field theory of mimetic gravity

Abstract: We discuss mimetic gravity theories with direct couplings between the curvature and higher derivatives of the scalar field, up to the quintic order, which were proposed to solve the instability problem for linear perturbations around the FLRW background for this kind of models. Restricting to homogeneous scalar field configurations in the action, we derive degeneracy conditions to obtain an effective field theory with three degrees of freedom. However, performing the Hamiltonian analysis for a generic scalar f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Note added: after the submission of this paper to arXiv, we note that a new paper [68] appeared. The authors in [68] discussed mimetic gravity theories with direct couplings between the curvature and higher derivatives of the scalar field only up to the quintic order. They first acquired effective field theories with three DOFs, and found that there are in general four or more DOFs for a generic scalar field.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Note added: after the submission of this paper to arXiv, we note that a new paper [68] appeared. The authors in [68] discussed mimetic gravity theories with direct couplings between the curvature and higher derivatives of the scalar field only up to the quintic order. They first acquired effective field theories with three DOFs, and found that there are in general four or more DOFs for a generic scalar field.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…However, in general its modified Einstein equation contains higher mixed derivatives of the metric in the synchronous frame t = φ. While it was found in [17] that these mixed derivatives can change the sign of the gradient term of scalar metric perturbations and help to prevent a gradient instability, it was later realized in [18], [19] that this comes at the price of introducing an additional hidden degree of freedom. Even tough this second scalar degree of freedom does not show up when perturbing around a homogeneous background in unitary gauge, it was found in [19] that already for perturbations around Minkowski spacetime with non-homogeneous mimetic field profile it can lead to instabilities.…”
Section: The Theorymentioning
confidence: 99%
“…While it was found in [17] that these mixed derivatives can change the sign of the gradient term of scalar metric perturbations and help to prevent a gradient instability, it was later realized in [18], [19] that this comes at the price of introducing an additional hidden degree of freedom. Even tough this second scalar degree of freedom does not show up when perturbing around a homogeneous background in unitary gauge, it was found in [19] that already for perturbations around Minkowski spacetime with non-homogeneous mimetic field profile it can lead to instabilities. Since this type of higher mixed derivatives is not present in L nhd , one could hope that no such additional degree of freedom will appear in this theory.…”
Section: The Theorymentioning
confidence: 99%
See 2 more Smart Citations